2012
DOI: 10.1152/jn.01028.2011
|View full text |Cite
|
Sign up to set email alerts
|

GABAA receptors increase excitability and conduction velocity of cerebellar parallel fiber axons

Abstract: Dellal SS, Luo R, Otis TS. GABA A receptors increase excitability and conduction velocity of cerebellar parallel fiber axons. J Neurophysiol 107: 2958 -2970. First published February 29, 2012 doi:10.1152/jn.01028.2011In the adult mammalian brain, GABA A receptors (GABA A Rs) are responsible for the predominant forms of synaptic inhibition, but these receptors can excite neurons when the chloride equilibrium potential (E Cl ) is depolarized. In many mature neurons, GABA A Rs are found on presynaptic terminals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 59 publications
(97 reference statements)
5
31
2
Order By: Relevance
“…Our previous work has demonstrated that activation of axonal GABA A Rs by exogenous GABA can affect AP firing in cerebellar granule cells (Pugh and Jahr, 2011). This result was confirmed by a computer modeling study of axonal GABA A R activation and AP initiation in the same cells (Dellal et al, 2012). To our knowledge, the present work is the first showing that activation of axonal receptors by release of neurotransmitter from nearby synapses can affect integration and AP initiation at the soma.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our previous work has demonstrated that activation of axonal GABA A Rs by exogenous GABA can affect AP firing in cerebellar granule cells (Pugh and Jahr, 2011). This result was confirmed by a computer modeling study of axonal GABA A R activation and AP initiation in the same cells (Dellal et al, 2012). To our knowledge, the present work is the first showing that activation of axonal receptors by release of neurotransmitter from nearby synapses can affect integration and AP initiation at the soma.…”
Section: Discussionsupporting
confidence: 85%
“…The excitability index of cells lacking an axon was significantly different from cells with an intact axon ( p ϭ 0.03, unpaired t test), confirming that the change in excitability results from axonal and not somatodendritic GABA A Rs. Previous work suggests that E Cl in parallel fibers is depolarized from rest, near AP threshold (Stell et al, 2007; Pugh and Jahr, 2011; Dellal et al, 2012). To mimic physiological conditions more closely, we repeated these experiments with a lower-chloride internal (E Cl of Ϫ50 mV).…”
Section: Activation Of Mlis By Chr2mentioning
confidence: 99%
See 1 more Smart Citation
“…Voltage-dependent increases of tonic conductance are expected to affect the behavior of hippocampal neurons and networks (Glykys and Mody 2006;Pavlov et al 2009). This would typically be an inhibitory effect, but if it occurred during periods of intracellular Cl Ϫ accumulation, voltage-dependent potentiation could enhance an excitatory influence of GABA currents (Dellal et al 2012;Dzhala et al 2010). Nonvesicular GABA release by GAT1.…”
Section: Discussionmentioning
confidence: 99%
“…In the cerebellum, a similar situation exists for locally released GABA onto parallel fibre axons [57]. Synaptic events that occur in dendrites can also passively propagate for very long distances down axons [34,37].…”
Section: Is This Form Of Information Processing Unique To the Gnrh Nementioning
confidence: 99%